V_rodents_snaptrapping_abundance_regional ... - Dorothee.Ehrich@Uit.No (UiT, 2025)
Snap trapping data of rodents on the Varanger and Nordkynn peninsula. This dataset has data from the COAT regional study design and has data on site-based abundances. Two related datasets have information on i) trapped individuals and ii) trap status, i.e. missing and closed traps. The dataset includes four different types of files and all files are saved as ;-separated txt-files: * One data file per year (_YEAR.txt) * One coordinate file with coordinates of all sites (_coordinates.txt) * One auxiliary file with information about which sites are included in the study design (_aux.txt) * One readme file with additional information (_readme.pdf) The dataset has a two-year embargo, older versions of the dataset are publicly available for download. ...